Method for regulating and controlling size of nanocellulose
By regulating the content of hemicellulose in the nanocellulose suspension and combining with multi-step processing, the size of nanocellulose was successfully adjusted, solving the problem of neglecting the influence of other components in the existing technology, and effectively controlling the size of nanocellulose is achieved .
Patent Information
- Application Number
- CN202411591329.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art ignores the influence of other components of lignocellulose itself on the diameter of nanocellulose when regulating the size of nanocellulose.
By regulating the content of hemicellulose in the nanocellulose suspension, combined with alkali treatment, bleaching treatment, alkali/urea treatment, TEMPO oxidation treatment and high-pressure homogenization treatment, the hemicellulose content in the nanocellulose suspension was prepared with a content of 6- 12 wt%, nanocellulose size is 1-5 nm.
The effective regulation of nanocellulose size by regulating the content of hemicellulose is achieved, providing a new method for the application of nanocellulose materials.
Smart Images

Figure CN119463214A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocellulose size regulation, and in particular to a method for regulating the size of nanocellulose by hemicellulose content. Background Art
[0002] Cellulose has the characteristics of abundant reserves, renewable, degradable and good biocompatibility, and is widely distributed in wood and bamboo resources. The nanocellulose prepared by removing lignin and hemicellulose from cellulose has nanometer size and extremely high mechanical properties, as well as a surface that is easy to chemically modify. Nanocellulose materials can be widely used in energy storage, textiles, optoelectronic devices, etc. In terms of regulating the size of nanocellulose, researchers often regulate the size of nanocellulose from aspects such as raw materials, degree of oxidation and high-pressure homogenization.
[0003] At present, researchers apply materials prepared from nanocellulose to energy storage and sensing. The current ways to improve and adjust the size of nanocellulose include: raw materials, oxidation degree and high-pressure homogenization. Zhou et al. oxidized different raw materials to obtain bacterial nanocellulose with a diameter of 18.6nm, sea squirt nanocellulose with a diameter of 7.1nm, and wood nanocellulose with a diameter of 2-5nm. Wu et al. increased the degree of oxidation by changing the amount of NaClO added, and obtained nanocellulose with different carboxyl contents. The diameter of 0.635mmol / g was 85nm, the diameter of 0.924mmol / g was 52nm, the diameter of 1.353mmol / g was 20nm, and the diameter of 1.646mmol / g was 6-10nm. Ji et al. changed the size of nanocellulose by different high-pressure homogenization times. The diameter was 100-300nm after 15 high-pressure homogenizations at 100MPa, and the diameter was 50-100nm after 20 high-pressure homogenizations.
[0004] The above methods for changing the size of nanocellulose mainly change the diameter of nanocellulose based on the differences in the raw materials themselves and the processing process, but ignore the influence of the presence of other components of cellulose itself on the diameter of nanocellulose. Summary of the invention
[0005] Based on the above content, the object of the present invention is to provide a method for regulating the size of nanocellulose.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A method for regulating the size of nanocellulose, wherein the size of nanocellulose is regulated by regulating the content of hemicellulose in a nanocellulose suspension;
[0008] The method for preparing the nanocellulose suspension comprises the following steps:
[0009] The biomass raw material is crushed and dried, and then subjected to alkali treatment, bleaching treatment, alkali / urea treatment, TEMPO oxidation treatment and high-pressure homogenization treatment in sequence to obtain a nanocellulose suspension;
[0010] The hemicellulose content in the nanocellulose suspension is 6-12 wt %, and the size of the nanocellulose is 1-5 nm.
[0011] In some embodiments of the present invention, the biomass raw material is at least one of bamboo, wood, reed, straw, wheat straw, bagasse or bamboo processing residues. More preferably, it is bamboo or bamboo processing residues; the bamboo is moso bamboo, cycad bamboo, white oleophyte bamboo, bamboo of green support, bamboo of balsam phoenix, pink single bamboo or green bamboo; the bamboo processing residues include but are not limited to bamboo pulp papermaking residues. The biomass raw material of the present invention can be selected from bamboo processing residues, so that resource utilization is improved.
[0012] In some embodiments of the present invention, the alkali treatment is to react in a NaOH solution with a mass concentration of 1 to 5% at 80°C for 1 to 2 hours; the number of alkali treatments is 1-2 times. Further preferably, the alkali treatment is to react in a NaOH solution with a mass concentration of 5% at 80°C for 1 hour. The present invention swells and disperses the bamboo fibers through alkali treatment, which is more conducive to subsequent bleaching treatment.
[0013] In some embodiments of the present invention, the bleaching treatment is carried out in a NaClO2 solution with a mass concentration of 1 to 3% at 60 to 80°C for 1 to 4 hours; more preferably, it is carried out in a NaClO2 solution with a mass concentration of 1.5% at 80°C for 1 hour. In the bleaching treatment of the present invention, lignin can be almost completely removed, and the present invention can achieve a better bleaching effect by using a relatively low concentration of NaClO2 treatment.
[0014] In some embodiments of the present invention, the alkali / urea treatment is to keep the mixture of sodium hydroxide and urea at a constant temperature of 30-50°C for 30 minutes; the concentration of NaOH in the mixture of sodium hydroxide and urea is 5-7wt%, and the concentration of urea is 1wt%. Further preferably, the alkali / urea treatment is to keep the mixture of sodium hydroxide and urea at a constant temperature of 40°C for 30 minutes; the concentration of NaOH in the mixture of sodium hydroxide and urea is 6wt%, and the concentration of urea is 1wt%. The alkali / urea treatment is performed 1-3 times.
[0015] The present invention further controls the hemicellulose content through alkali / urea treatment. The concentration of alkali and urea, the treatment temperature, and the number of treatments will affect the hemicellulose content. When the concentration of alkali and urea is too high, the cellulose will be degraded, thereby reducing the yield and increasing the hemicellulose content. When the temperature and the number of treatments are higher than the above parameter ranges, the cellulose will also be degraded, thereby increasing the hemicellulose content.
[0016] In some embodiments of the present invention, the TEMPO oxidation treatment is to react in a mixed solution containing TEMPO, NaBr and NaClO for 1-5h; the amount of TEMPO is 0.015g / g biomass raw material; the amount of NaBr is 0.1g / g biomass raw material; the amount of NaClO is 4-12mmol / g biomass raw material. Further preferably, the TEMPO oxidation treatment is to react in a mixed solution containing TEMPO, NaBr and NaClO for 5h; the amount of TEMPO is 0.015g / g biomass raw material; the amount of NaBr is 0.1g / g biomass raw material; the amount of NaClO is 10mmol / g biomass raw material. Nanocellulose with a higher carboxyl content can be obtained by TEMPO oxidation.
[0017] In some embodiments of the present invention, the high-pressure homogenization treatment is 600-2000 bar homogenization for 5-8 times. More preferably, the high-pressure homogenization treatment is 1800 bar homogenization for 5 times. The present invention can obtain a uniformly dispersed and transparent nanocellulose suspension through high-pressure homogenization. The present invention does not specifically limit the instrument used for high-pressure homogenization, and conventional technical means of those skilled in the art can be selected, such as a high-pressure homogenizer.
[0018] The present invention achieves a hemicellulose content of 6-12wt% in the nanocellulose suspension and regulates the size of the nanocellulose to 1-5nm through the coordination of the steps of alkali treatment, bleaching treatment, alkali / urea treatment, TEMPO oxidation treatment and high-pressure homogenization treatment and strict control of parameters in the process of each treatment step. The present invention provides a new method for regulating the size of nanocellulose.
[0019] The present invention discloses the following technical effects:
[0020] Different from the prior art which regulates the size of nanocellulose by adjusting the raw materials, oxidation degree and high-pressure homogenization, the present invention regulates the size of nanocellulose by regulating the content of hemicellulose, thereby providing a new method for regulating the size of nanocellulose. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 IR spectra of nanocellulose with different hemicellulose contents in Examples 1-3;
[0023] Figure 2 The rheological test graphs of the nanocellulose suspensions of Examples 1-3;
[0024] Figure 3 is the gel state of the nanocellulose suspension of Examples 1-3;
[0025] Figure 4 AFM images of the nanocellulose suspensions of Examples 1-3;
[0026] Figure 5 Statistical diagram of the distribution of nanocellulose diameters in the nanocellulose suspensions of Examples 1-3;
[0027] Figure 6 Stress-strain curves of macrofibers were prepared for the nanocellulose suspensions of Examples 1-3. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0034] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0035] Example 1
[0036] (1) breaking up the bamboo with a wall breaking machine, drying, and obtaining bamboo raw fibers;
[0037] (2) placing the raw bamboo fiber in a 5 wt% NaOH solution, reacting it in a water bath at 80° C. for 1 h, and washing it to neutrality after cooling;
[0038] (3) Bleaching treatment: adding the product obtained in step (3) to a 1.5 wt% NaClO2 solution, adjusting the pH to between 4.6 and 5, reacting in a water bath at 80°C for 1 hour, and then washing to neutrality;
[0039] (4) Alkali / urea treatment: the product obtained in step (4) was added to a mixed solution of sodium hydroxide and urea (the concentration of NaOH in the mixed solution was 6 wt % and the concentration of urea was 1 wt %), placed in a 40° C. constant temperature water bath for reaction for 30 min, and then washed until neutral; step (4) was repeated twice;
[0040] (5) The product obtained in step (5) is reacted in a mixed solution containing TEMPO, NaBr and NaClO (the amount of TEMPO is 0.015 g / g of moso bamboo fiber; the amount of NaBr is 0.1 g / g of moso bamboo fiber; the amount of NaClO is 10 mmol / g of moso bamboo fiber) for 5 hours, and then the obtained reaction solution is diluted to a nanocellulose concentration of 1 wt%, and then high-pressure homogenization is performed at 1800 bar for 5 times to obtain a nanocellulose suspension uniformly dispersed in an aqueous solution.
[0041] The hemicellulose content in the nanocellulose suspension is 6.79 wt %, and the diameter of the nanocellulose is distributed in the range of 1-3 nm.
[0042] The nanocellulose suspension was squeezed into a methanol coagulation bath through a microinjection pump to form it. After 1 minute, it was pulled up to prepare nanocellulose macrofibers, which were dried in an oven at 100°C. The mechanical properties were tested, and the tensile strength was 11.6 GPa and the tensile stress was 244 MPa.
[0043] Example 2
[0044] (1) breaking up the bamboo with a wall breaking machine, drying, and obtaining bamboo raw fibers;
[0045] (2) placing the raw bamboo fiber in a 5 wt% NaOH solution, reacting it in a water bath at 80° C. for 1 h, and washing it to neutrality after cooling;
[0046] (3) Bleaching treatment: adding the product obtained in step (3) to a 1.5 wt% NaClO2 solution, adjusting the pH to between 4.6 and 5, reacting in a water bath at 80°C for 1 hour, and then washing to neutrality;
[0047] (4) Alkali / urea treatment: the product obtained in step (4) was added to a mixed solution of sodium hydroxide and urea (the concentration of NaOH in the mixed solution was 6 wt % and the concentration of urea was 1 wt %), placed in a constant temperature water bath at 40° C. for reaction for 30 min, and then washed until neutral; step (4) was repeated once;
[0048] (5) The product obtained in step (5) is reacted in a mixed solution containing TEMPO, NaBr and NaClO (the amount of TEMPO is 0.015 g / g of moso bamboo fiber; the amount of NaBr is 0.1 g / g of moso bamboo fiber; the amount of NaClO is 10 mmol / g of moso bamboo fiber) for 5 hours, and then the obtained reaction solution is diluted to a nanocellulose concentration of 1 wt%, and then high-pressure homogenization is performed at 1800 bar for 5 times to obtain a nanocellulose suspension uniformly dispersed in an aqueous solution.
[0049] The hemicellulose content in the nanocellulose suspension is 8.98 wt %, and the diameter of the nanocellulose is distributed in the range of 1-4 nm.
[0050] The nanocellulose suspension was squeezed into a methanol coagulation bath through a microinjection pump to form it. After 1 minute, it was pulled up to prepare nanocellulose macrofibers, which were dried in an oven at 100°C. The mechanical properties were tested, and the tensile strength was 9.4 GPa and the tensile stress was 169 MPa.
[0051] Example 3
[0052] (1) breaking up the bamboo with a wall breaking machine, drying, and obtaining bamboo raw fibers;
[0053] (2) placing the raw bamboo fiber in a 5 wt% NaOH solution, reacting it in a water bath at 80° C. for 1 h, and washing it to neutrality after cooling;
[0054] (3) Bleaching treatment: adding the product obtained in step (3) to a 1.5 wt% NaClO2 solution, adjusting the pH to between 4.6 and 5, reacting in a water bath at 80°C for 1 hour, and then washing to neutrality;
[0055] (4) Alkali / urea treatment: the product obtained in step (4) was added to a mixed solution of sodium hydroxide and urea (the concentration of NaOH in the mixed solution was 6 wt % and the concentration of urea was 1 wt %), placed in a constant temperature water bath at 40° C. for reaction for 30 min, and then washed until neutral;
[0056] (5) The product obtained in step (5) is reacted in a mixed solution containing TEMPO, NaBr and NaClO (the amount of TEMPO is 0.015 g / g of moso bamboo fiber; the amount of NaBr is 0.1 g / g of moso bamboo fiber; the amount of NaClO is 10 mmol / g of moso bamboo fiber) for 5 hours, and then the obtained reaction solution is diluted to a nanocellulose concentration of 1 wt%, and then high-pressure homogenization is performed at 1800 bar for 5 times to obtain a nanocellulose suspension uniformly dispersed in an aqueous solution.
[0057] The hemicellulose content in the nanocellulose suspension is 11.21 wt%, and the diameter of the nanocellulose is distributed in the range of 1-5 nm.
[0058] The nanocellulose suspension was squeezed into a methanol coagulation bath through a microinjection pump to form it. After 1 minute, it was pulled up to prepare nanocellulose macrofibers, which were dried in an oven at 100°C. The mechanical properties were tested, and the tensile strength was 7.8 GPa and the tensile stress was 89 MPa.
[0059] Table 1 shows the fiber composition after three different times of treatment according to the present invention.
[0060] Table 1
[0061]
[0062]
[0063] Figure 1 (In the figure, F-6.79 represents Example 1, F-8.98 represents Example 2, and F-11.21 represents Example 3) is the infrared spectra of nanocellulose with different hemicellulose contents in Examples 1 to 3. Through infrared testing, the difference in hemicellulose content can be clearly seen.
[0064] Figure 2 (In the figure, CNF-6.79 represents Example 1, CNF-8.98 represents Example 2, and CNF-11.21 represents Example 3) is a rheological test diagram of the nanocellulose suspensions of Examples 1 to 3. It can be seen that the sample of Example 3 has the highest viscosity.
[0065] Figure 3 (In the figure, CNF-6.79 represents Example 1, CNF-8.98 represents Example 2, and CNF-11.21 represents Example 3) is the gel state of the nanocellulose suspension of Examples 1 to 3. It can be seen that the gel state of the sample of Example 3 is stronger.
[0066] Figure 4 (In the figure, CNF-6.79 represents Example 1, CNF-8.98 represents Example 2, and CNF-11.21 represents Example 3) is an AFM image of the nanocellulose suspensions of Examples 1 to 3. It can be seen that the sample of Example 3 has a lower diameter.
[0067] Figure 5 (In the figure, CNF-6.79 represents Example 1, CNF-8.98 represents Example 2, and CNF-11.21 represents Example 3) is a statistical diagram of the distribution of nanocellulose diameters in the nanocellulose suspensions of Examples 1 to 3. It can be seen that the sample of Example 3 is more distributed in the low diameter range.
[0068] Figure 6 (In the figure, CNF-6.79 represents Example 1, CNF-8.98 represents Example 2, and CNF-11.21 represents Example 3) are macroscopic fiber stress-strain curves prepared from nanocellulose in the nanocellulose suspensions of Examples 1 to 3. It can be seen that the sample of Example 3 has better mechanical properties.
[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for regulating the size of nanocellulose, characterized in that: The size of nanocellulose can be controlled by regulating the content of hemicellulose in the nanocellulose suspension; The method for preparing the nanocellulose suspension comprises the following steps: The biomass raw material is crushed and dried, and then subjected to alkali treatment, bleaching treatment, alkali / urea treatment, TEMPO oxidation treatment and high-pressure homogenization treatment in sequence to obtain a nanocellulose suspension; The hemicellulose content in the nanocellulose suspension is 6-12 wt %, and the size of the nanocellulose is 1-5 nm.
2. The method for regulating the size of nanocellulose according to claim 1, characterized in that: The biomass raw material is at least one of bamboo, wood, reed, straw, wheat straw, bagasse or bamboo processing residues.
3. The method for regulating the size of nanocellulose according to claim 1, characterized in that: The alkali treatment is carried out in a NaOH solution with a mass concentration of 1 to 5% at 80° C. for 1 to 2 hours; the alkali treatment is performed 1 to 2 times.
4. The method for regulating the size of nanocellulose according to claim 1, characterized in that: The bleaching treatment is carried out in a NaClO2 solution with a mass concentration of 1 to 3% at 60 to 80°C for 1 to 4 hours.
5. The method for regulating the size of nanocellulose according to claim 1, characterized in that: The alkali / urea treatment is carried out in a mixed solution of sodium hydroxide and urea at a constant temperature of 30-50°C for 30 minutes; the concentration of NaOH in the mixed solution of sodium hydroxide and urea is 5-7wt%, and the concentration of urea is 1wt%; the number of times of the alkali / urea treatment is 1-3 times.
6. The method for regulating the size of nanocellulose according to claim 1, characterized in that: The TEMPO oxidation treatment is to react in a mixed solution containing TEMPO, NaBr and NaClO for 1-5h; the amount of TEMPO used is 0.015g / g biomass raw material; the amount of NaBr used is 0.1g / g biomass raw material; the amount of NaClO used is 4-12mmol / g biomass raw material.
7. The method for regulating the size of nanocellulose according to claim 1, characterized in that: The high pressure homogenization process is 600-2000 bar homogenization 5-8 times.
Citation Information
Patent Citations
Method for spinning nanocellulose suspension through low-concentration ionic solution
CN118272938A